2000
DOI: 10.1093/oxfordjournals.molbev.a026395
|View full text |Cite
|
Sign up to set email alerts
|

Enolase from Trypanosoma brucei, from the Amitochondriate Protist Mastigamoeba balamuthi, and from the Chloroplast and Cytosol of Euglena gracilis: Pieces in the Evolutionary Puzzle of the Eukaryotic Glycolytic Pathway

Abstract: Genomic or cDNA clones for the glycolytic enzyme enolase were isolated from the amitochondriate pelobiont Mastigamoeba balamuthi, from the kinetoplastid Trypanosoma brucei, and from the euglenid Euglena gracilis. Clones for the cytosolic enzyme were found in all three organisms, whereas Euglena was found to also express mRNA for a second isoenzyme that possesses a putative N-terminal plastid-targeting peptide and is probably targeted to the chloroplast. Database searching revealed that Arabidopsis also possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 73 publications
5
60
1
1
Order By: Relevance
“…First, although archaebacteria possess pathways from glucose to pyruvate, they have several alternative pathways that involve different enzymatic steps, hence different enzymes not present in glycolysis (Daniel & Danson 1995;Schö nheit & Schäfer 1995;Kengen et al 1996;Selig et al 1997). These include: (i) the modified Embden-Meyerhof pathway, which employs ADP-instead of ATP-dependent steps and a glyceraldehyde-3-phosphate oxidoreductase in place of the steps catalysed by GAPDH and 3-phosphoglycerate kinase; (ii) the Entner-Doudoroff pathway, which does not require the enzymatic steps catalysed by GPI, PFK, FBA or TPI; and (iii) the non-phosphorylated Entner-Doudoroff pathway, which shares only two enzymatic steps in common with glycolysis (Selig et al 1997), those catalysed by enolase (Hannaert et al 2000) and pyruvate kinase (Schramm et al 2000). Second, several archaebacteria have complete glycolytic pathways, but for many steps they use totally different enzymes that are unrelated to the familiar homologues found in eubacteria (and eukaryotes) (Schö nheit & Schäfer 1995;Selig et al 1997).…”
Section: Commonalities and Differences Lead Quickly To Deeper Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, although archaebacteria possess pathways from glucose to pyruvate, they have several alternative pathways that involve different enzymatic steps, hence different enzymes not present in glycolysis (Daniel & Danson 1995;Schö nheit & Schäfer 1995;Kengen et al 1996;Selig et al 1997). These include: (i) the modified Embden-Meyerhof pathway, which employs ADP-instead of ATP-dependent steps and a glyceraldehyde-3-phosphate oxidoreductase in place of the steps catalysed by GAPDH and 3-phosphoglycerate kinase; (ii) the Entner-Doudoroff pathway, which does not require the enzymatic steps catalysed by GPI, PFK, FBA or TPI; and (iii) the non-phosphorylated Entner-Doudoroff pathway, which shares only two enzymatic steps in common with glycolysis (Selig et al 1997), those catalysed by enolase (Hannaert et al 2000) and pyruvate kinase (Schramm et al 2000). Second, several archaebacteria have complete glycolytic pathways, but for many steps they use totally different enzymes that are unrelated to the familiar homologues found in eubacteria (and eukaryotes) (Schö nheit & Schäfer 1995;Selig et al 1997).…”
Section: Commonalities and Differences Lead Quickly To Deeper Problemsmentioning
confidence: 99%
“…This approach to the holochirality problem implicates the peptidyl transferase reaction of the ribosome as the pacemaker for amino-acid stereochemistry and a simpler precursor of enolase as the pacemaker of sugar stereochemistry. It is probably just curious coincidence that enolase is the only enzyme of carbon metabolism, other than adenylate kinase, that balances AMP, ADP and ATP levels, that is encoded in the highly conserved ribosomal protein superoperon in archaebacteria (Hannaert et al 2000), which might also carry a faint trace of chiral origins. At any rate, our suggestion for the origin of holochirality starts with the peptidyl transferase reaction and is thus largely congruent with Woese's (2002, p. 8745) assessment 'The evolution of modern cells, then, had to begin with the onset of translation'.…”
Section: Holochiralitymentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of PDH Subunits E1␣, E2, and E3-Standard molecular methods, nucleic acid isolation, cDNA synthesis, and cloning in ZAPII were performed as described previously (36,37). Hybridization probes for PDH subunits from Euglena were obtained by comparisons of in-house Euglena EST data with annotated sequences in the National Center for Biotechnology Information data base using BLAST.…”
Section: In-gel Digestion and Esi-q-tof-ms/msmentioning
confidence: 99%
“…However, a few proteins belonging to other functional classes, notably adenylate kinase (Sa! nchez & Mu $ ller, 1998) and enolase (Hannaert et al, 2000) involved in energy metabolism, are also found in the cluster in some genomes (Wa$ chtersha$ user, 1998). This cluster has proven useful from the standpoint of plastid phylogeny by virtue of its tendency to preserve gene order, revealing evolutionary relationships among plastids (Stoebe & Kowallik, 1999 (Wa$ chtersha$ user, 1998).…”
mentioning
confidence: 99%